The effect of association, ability, and credibility of companies implementing CSR on the analysts’ investment recommendations - Chindi Nurkholiva S (Universitas Hayam Wuruk Perbanas, 2014)
The awareness of the importa nce of social responsibility among companies has recently improved significantly. The goal is to increase the profit, which, in turn, to maintain the sustainability of the company. Corporate Social Responsibility (CSR) is not new in the world of business. The perception which states that analysts would provide a good assessment to companies for supporting CSR activities has prompted several companies to adopt CSR for their daily activities. This study uses the sample of brokers or stock analysts taken by using questionnaires. The stock analysts are divided into two groups. The first group is the stock analysts who know about the company's CSR but do not follow the development. The second group is the stock analysts who know and follow the development. The data in this study were analyzed using multiple linear regressions. The result shows that for the first group, it is only credibility variable which significantly affects the analysts’ investment recommendations, while for the second group; it is only association variable which significantly affects the analysts’ investment recommendations.